Influence of Digital Marketing, Brand Image, and Service Quality on Nasabah Decision to Use Indonesia Syariah Bank Services (Case Study of Generation Z in Tegal City) - Alawiyah, Nafisatul; Mohammad Rosyada (Wealth: Journal of Islamic Banking and Finance, 2025)
Digital transformation in the Industrial Revolution 4.0 era has driven the banking sector, including BSI, to offer technology-based services such as the BYOND by BSI application. Generation Z is the main target due to their high digital engagement. However, their interest and understanding of Islamic banking remain varied, especially in Tegal City, where participation is still low despite a Muslim majority. This study analyzes the influence of digital marketing, brand image, and service quality on Generation Z’s decision to use BSI services in Tegal City. This research employed a quantitative approach with a survey method and associative causal type. The population comprised Generation Z aged 18–28 years, with a sample of 96 respondents selected through purposive sampling. Data were collected using a questionnaire with Likert scale and analyzed through validity, reliability, classical assumption tests, multiple linear regression, and hypothesis testing with SPSS. The results indicate that digital marketing and service quality have a positive and significant effect on Generation Z’s decision to use BSI services, while brand image does not have a significant partial effect. However, simultaneously, the three variables have a positive and significant influence. These findings suggest that strengthening digital marketing strategies and improving service quality are dominant factors in influencing young customers’ decisions.